A Study of the Physiological Effects of the Anticancer Paclitaxel in Men - Baida Rihan Ali Rihan Ali (Al-Qadisiyah Journal of Pure Science, 2017)
The present study aims to investigate the effect of Paclitaxel drug on hematological, biochemical parameters and sex hormones of men. Adult men divided into two groups for each sex (33 for each group), the first group (control) and the second group treatment with Paclitaxel drug. Results study indicated a significant decrease (Pâ‰¤0.05) in red blood cell count (RBC), packed cell volume (PCV), Total white blood cell count (WBC) and LH level in the men to second group compared with the control group. Also, it showed a significant increase (pâ‰¤ 0.05) in Creatinine and urea levels to second group compared with the control group. Also, the result showed non-significant in FSH levels to mean in control and second groups.